Warm-up optimization in amateur male soccer players: A comparison of small-sided games and traditional warm-up routines on physical fitness qualities - Thapa, Rohit; Clemente, Filipe; Moran, Jason; Garcia-Pinillos, Felipe; T. Scanlan, Aaron; Ramirez-Campillo, Rodrigo (Biology of Sport, 2023)
The aim of this study was to compare the effects of small-sided soccer games (SSSGs) and traditional warm-up (TWU) routines on physical fitness qualities in soccer players. Following a between-subject, randomized design, amateur-levelsoccer players were assigned to a SSSG warm-up (n = 10; age: 19.3±2.8 years) or TWU group (n = 10; age: 19.3±2.4 years). Players completed multiple trials of 10-m and 30-m linear sprints, change-of-direction speed (CODS) tests, and countermovement jumps (CMJ) prior to and following the warm-up routine. Separate mixed ANOVAs were performed to assess group effects (SSSG vs. TWU), time effects within each group (pre- vs. post-warm-up), and their interaction for each physical fitness quality. No significant interaction effects were observed for any dependent variable. Significant improvements were evident between baseline and follow-up measurements for 10-m sprint time (p = 0.002, Hedges’ g effect size [g] = 0.59) and CMJ variables (height: p = 0.016, g = 0.20; power: p = 0.003, g = 0.19; force: p = 0.002, g = 0.14) in the TWU group and for CODS performance time (p = 0.012, g = 0.51) and CMJ variables (height: p < 0.001, g = 0.46; power: p = 0.002, g = 0.35; force: p = 0.001, g = 0.27) in the SSSG warm-up group. Both SSSG and TWU protocols improved selected physical fitness qualities with SSSG more effective at improving CODS and CMJ performance, and TWU more effective at improving linear speed. Soccer coaches may choose between SSSG or traditional warm-up activities according to player needs and preferences; however, the superior effects of SSSG suggest it might offer greater benefits than TWU in preparing players for optimal physical output.